Pengaruh Religiusitas, Kecerdasan Emosional dan Dukungan Sosial Keluarga Terhadap Resiliensi Siswa Kelas VII SMP IT Masjid Syuhada Yogyakarta Tahun Pelajaran 2019/2020 - Arifin, Samsul (Islamic Education, 2022)
This study aims to determine the influence of religiosity, emotional intelligence, and family social support on the resilience of seventh-grade students at SMP IT Masjid Syuhada Yogyakarta for the 2019/2020 academic year. The method used in this research is a quantitative method, which analyzes the influence of the independent variables (religiosity, emotional intelligence, and family social support) on the dependent variable (resilience). The research data were collected through questionnaires filled out by 60 students, representing 54% of the total population of 112 students. The analysis results show that religiosity, emotional intelligence, and family social support significantly influence students' resilience, contributing 90.8%. These findings highlight the importance of these three factors in building and strengthening students' resilience. This study provides practical implications for educators and parents in their efforts to enhance students' resilience by improving religiosity, emotional intelligence, and family social support.